Desenvolvimento osteológico de Hippocampus reidi Ginsburg (Pisces, Syngnathiformes, Syngnathidae), em laboratório: II. Período juvenil - Silveira,Rosana Beatriz (2000)
The sequence of events of the ossification process in the newly bom specimens of Hippocampus reidi Ginsburg, 1933 up to 37 days of life has been described, mainly the ossification in the ethmoid plate, palatine, pectoral girdle, and postorbital bones and bony structures such as mesoethmoid, articular and six suborbitals. Observation on adult specimens are presented too.